VISUALISASI PERADABAN ISLAM: STUDI HISTORIS DAN UPAYA KONSERVASI MANUSKRIP DI MUSEUM SEJARAH AL-QUR’AN SUMATERA UTARA - Alfreido Simatupang; Charmelita Simbolon; Fatih Ilham Ismail; Sarah Fadillah; Syifa Ramadani; Ika Purnamasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the visualization of Islamic civilization through Qur’anic manuscripts and to examine the conservation efforts carried out at the Museum of Qur’anic History in North Sumatra. Qur’anic manuscripts do not merely function as religious texts, but also serve as representations of Islamic civilization, reflecting the intellectual, artistic, and cultural development of Muslim societies. This research employs a qualitative descriptive method, with data collection techniques including observation, interviews, and documentation. The results indicate that Qur’anic manuscripts in North Sumatra possess distinctive characteristics, such as specific calligraphic styles, locally influenced illumination patterns, and the use of traditional writing materials. Conservation efforts undertaken by the museum include physical preservation, environmental control, and digitization. However, several challenges remain, including limited facilities, lack of expert personnel, and low public awareness. Therefore, more comprehensive strategies are needed to enhance the preservation of manuscripts as part of the heritage of Islamic civilization.